Answer:
(2x - 3)⁵= 32x⁵ - 240x⁴ + 720x³ - 1080x² + 810x - 243
Explanation:
We need to write the expansion of Binomial (2x - 3)⁵
Here general form of binomial expansion is:
(a + b)ⁿ = ⁿC₀aⁿ + ⁿC₁aⁿ⁻¹b + ⁿC₂aⁿ⁻²b² + ⁿC₃aⁿ⁻³b³ + ... + ⁿCₙbⁿ
(2x - 3)⁵= ⁵C₀(2x)⁵ + ⁵C₁(2x)⁵⁻¹(-3) + ⁵C₂(2x)⁵⁻²(-3)² + ⁵C₃(2x)⁵⁻³(-3)³
+⁵C₄(2x)⁵⁻⁴(-3)⁴ + ⁵C₅(2x)⁵⁻⁵(-3)⁵
(2x - 3)⁵= (32x⁵) + 5(16x⁴)(-3) + 10(8x³)(-3)² + 10(4x²)(- 3)³ + 5(2x)(-3)⁴+(-3)⁵
(2x - 3)⁵= 32x⁵ - 240x⁴ + 720x³ - 1080x² + 810x - 243
That's the final answer.